The The Relationship between Parenting, Exclusive Breasting and Quality of MP-ASI with Stunting Incidence in Under-Free Children Aged 6-12 Months - Sari, Wina Puspita; Maigoda, Tonny Cortis (JURNAL PROTEKSI KESEHATAN, 2023)
Stunting is short stature that arises as a result of prolonged malnutrition. The indicator was the index (PB/U) according to WHO standards with growth criteria if the z-score PB/U -3 SD <-2 SD Based on the results of a nutritional status survey in the Bengkulu City Health Office in 2022, the highest prevalence was in the Sawah Lebar Health Center WAS 15 children. The puprpose of the study was to determine the relationship between parenting style, exclusive breastfeeding and the quality of MP-asi with the incidence of stunting in toddlers aged 6-12 months in the working area of the Sawah Lebar Public Health Center in Bengkulu City in 2023. The research design was cross sectional. The sampling technique was simple random sampling, with a total sample was 59 toddlers. Collecting data with observational questionnairy. Chi square test was used in statistical analysis. The results showed that there was a relationship between parenting style, exclusive breastfeeding, and the quality of MP-ASI with the prevalence of stunting (p <0.05) in toddlers aged 6-12 months. It is recommended to examine other factors that will lead to stunting such as family income, the number of family members and food intake.